Pengenalan Dan Perawatan Gigi Pada Anak Menggunakan Markerless Augmented Reality - Dwi Rezki Agung; Anang Kukuh Adisusilo; Beny YV Nasution (Informatics Engineering Department-UWKS, 2015)
Teeth is an important part in the oral cavity, because of the function of the tooth that is not replaceable. The composition of the teeth in children are primary teeth in adults are permanent teeth. The introduction and dental care at an early age is very important to help maintain the health of their teeth. In fact, it is still prevalent learning process and the introduction of dental care less interactive and have less traction, even tend to be boring so the learning outcomes achieved are not optimal. Besides learning in children is not as easy as it provides learning materials teenage school or next higher level, because it takes a medium for children as learning with interactive concept with digital learning media Augmented Reality. The purpose of the research that is changing the look of learning recognition and the procedures for the care of teeth with AR technology and utilization of technology Markerless as an AR marker. Results of testing applications on Windows-based operating systems can run well, and the test results on the SDN Dukuh Kupang II-489 Surabaya showed a percentage of more than 88% chose interested to learn about teeth and dental care procedures for using applications that have been tested.